Special considerations for designing wrestling-specific resistance-training programs - Murlasits, Z. (Strength and Conditioning Journal, 2004)
The sport of wrestling presents several challenges to the strength and conditioning professional, such as bodyweight restriction, concurrent strength and endurance training, specific injury patterns, and unique metabolic demands, which can be resolved by designing the resistance-training program to match these requirements. This article offers recommendations for the implementation of an effective resistance-training program for wrestling